If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x-10=0.5(8x+10)
We move all terms to the left:
7x-10-(0.5(8x+10))=0
We calculate terms in parentheses: -(0.5(8x+10)), so:We get rid of parentheses
0.5(8x+10)
We multiply parentheses
4x+5
Back to the equation:
-(4x+5)
7x-4x-5-10=0
We add all the numbers together, and all the variables
3x-15=0
We move all terms containing x to the left, all other terms to the right
3x=15
x=15/3
x=5
| 15=j-12 | | x-7/44=-3/11 | | 1=3(n+5)=-8 | | Y=0.6-0.005x | | 7y+4=22 | | 2(-4x+7)=30 | | 46=z2.5 | | 3/x-2=0 | | 47=s/9+39 | | 3x+9=68 | | -f/8+4=7 | | 8(20-x)=40 | | 11m-4+3m=-4m+9+18m | | 4/8n=-1/4 | | Y=0.7-0.005x | | -16=-42g+68 | | y/7+24=27 | | 3x−5=−5+2x | | 7(y-92)=21 | | 3x+3+3x+3+3x-5+3x-5=32 | | (5x+62)+(3x+47)=180 | | 3x=9=24x= | | t-88/5=2 | | 7y+8-4y=6+3y | | 11.2=7i | | 3x+5=9×-17 | | -125p-6=25p-300 | | 5=c+6/4 | | -h-18=17 | | -3m+8m=-20 | | 9w+8.5=14 | | 21=2y-3 |